Pengaruh Jumlah Agkatan Kerja Dan Pertumbuhan Ekonomi Terhadap Tingkat Pengangguran Terdidik Di Sulawesi Tenggara - Santri, Dewi; Sari, Kiki Novita; Octaviana, Nur Alfira (IAIN Kendari, 2024)
Educated unemployment has always been a complex problem that requires serious handling by the government. It is necessary to know what factors influence the level of educated unemployment in Indonesia to make it easier for the government to handle it. Some literature states that the size of the workforce and economic growth also influence the unemployment rate. This research aims to analyze the influence of the size of the workforce and economic growth on the level of educated unemployment in Southeast Sulawesi. The research was carried out using multiple linear regression analysis using data from 2012 to 2021. The results of the research show that the two variables, both the number of the workforce and economic growth, do not have a significant effect on educated unemployment in Southeast Sulawesi. The increase in the workforce in Southeast Sulawesi does not affect the unemployment rate. And the level of economic growth represented by GRDP does not necessarily reduce the number of unemployed significantly.